Does muscle fatigue influence swimming performance? - Andrade, R.; Figueira, A.; Flavio, A. L. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose to determine the influence of lower limbs muscle fatigue upon swimming performance (SP) in adult subjects. The data found allowed the authors to conclude that maximal strength, or strength plato output during repeated contractions, seems to be more important to swimmers muscle power.